Poster 244: Pain Catastrophizing in Patellar Instability Patients Undergoing MPFL Reconstruction. Issue 7 (30th July 2022) - Zavras, Athan; Trasolini, Nicholas; Walsh, Justin; Yanke, Adam; Dandu, Navya
Objectives: Pain catastrophizing was established as a way to measure patient perception and response to pain, as represented by three subscores: rumination, magnification, and helplessness. Prior clinical studies have demonstrated the close relationship between pain catastrophizing and persistent postoperative pain after total knee arthroplasty. Among patellofemoral instability patients, pain catastrophizing has also been investigated. However, specific patient factors that contribute to greater degrees of pain catastrophizing in patellofemoral instability are not yet understood. Additionally, investigations of the association between preoperative catastrophizing and postoperative pain are limited. Therefore, the purpose of this study is to investigate risk factors for higher preoperative pain catastrophizing and its correlation with pain scores following medial patellofemoral ligament reconstruction (MPFLR). Methods: This study retrospectively evaluated patients who underwent MPFLR between 2015 and 2020 with preoperative pain catastrophizing scores (PCS). Patient demographics were collected to evaluate risk factors for worse PCS scores. Four overlapping questions from the KOOS JR and full KOOS questionnaires were utilized at the preoperative and 6 months postoperative time points to assess pain on a scale from 0 (least) to 4 (most), including pain with: 1.) Knee Twisting, 2.) Knee Straightening, 3.) Stair Climbing, and 4.) Standing Upright. Results: Thirty-four patients were included for analysis. Higher age at the time of surgery was significantly associated with worse Helplessness (R 2 =0.11, p=.035), Rumination (R 2 =0.18, p=.020), and Total PCS scores (R 2 =0.08, p=.039). Patients with >5 instability events reported significantly worse Rumination (2.29±2.87 vs 4.60±3.31, p=.049). At 6 months post-operatively, 32.35% of patients (11/34) continued to report moderate pain in at least one pain category. These patients reported significantly greater Rumination at baseline (2.91 ± 3.37 vs 6.64 ± 5.22, p = .017). Lastly, higher baseline Helplessness significantly correlated with greater improvement in pain with stairs (p = .049), higher Magnification significantly correlated with greater improvement in pain with standing (p = .012), and higher baseline Total PCS correlated with more improvement in pain with stairs (p = .035) and standing (p = .037). Multivariate analysis demonstrated that history of prior surgery and age remained independently predictive of postoperative pain scores (Table 1 ). Conclusions: Older age and >5 instability events at presentation were patient risk factors associated with increased pain catastrophizing. Pain catastrophizing had different correlations with postoperative pain depending on subscore, with higher Rumination associated with persistent moderate pain while higher Magnification or Helplessness correlated with greater improvement in pain. However, on multivariate analyses the only significant independent predictors of persistent moderate to severe post-operative pain at 6 months were age and history of prior surgery. Further investigation is needed to determine whether pain catastrophizing is an innate patient factor with post-operative implications or merely an effect of prolonged symptoms in patellar instability patients. Table 1. Multivarite Linear regression model evaluating indepentant predictors of worse postoperative pain scores